The Effectiveness of Using Sequence Picture Media in Teaching EFL Students in Writing Procedure Text - Jonris Tampubolon; Edi Suprayetno (Journal of Applied Linguistics, 2022)
Teaching EFL students are both challenging and demanding as English is neither the students’ mother tongue nor their second language. Therefore, it is essentially required to select an effective way or technique in achieving the objectives of the lesson. This study was aimed to investigate the use of sequence picture technique and its effectiveness in teaching EFL students how to write a procedure text. This study was conducted by using quantitative research with one group pretest-posttest design at Universitas Prima Indonesia. The steps involve administering pretest measuring the dependent variable, applying the experimental treatment X to the subjects; and administering a posttest again measuring the dependent variable. There were 40 students taken as the subject of the study. The data were collected through a pretest and a posttest. The result on this study showed that the students’ responses and performances were improved. It can be seen from the finding which showed that students’ percentage in using the language components such as grammar, sequence words, commands or imperative sentences, and adverbial phrases accurately. The result of the questionnaire also showed that the students considered sequence picture technique was effective in helping them write procedure text correctly.        Key Words: EFL Students, Procedure Text, Sequence Picture Media